2005
DOI: 10.1016/j.electacta.2005.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an electroactive polymer for overcharge protection in secondary lithium batteries

Abstract: The optical, electronic, and electrochemical properties of thin films of the electroactive polymer, poly(3-butylthiophene) (P3BT), were studied in a lithium hexafluorophosphate electrolyte. Upon extraction of n electrons per polymer formula unit, anions are taken up to balance the charge, forming a polymer cation salt, (P3BT) mn+ (PF 6 -) mn (m is the number of formula units in the polymer chain), whose state of charge (SOC) varies with n. An in situ AC impedance method was developed to determine the electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…The steady state potential increased with the charging rate, resulting in increased oxidation (and electronic conductivity) of the polymers. 7 At a current density of 1.0 mA/cm 2 (2.7 C), the separator was able to maintain a voltage of 4.6 V. In this configuration, however, a steady state potential could not be maintained above…”
Section: Rate Capability Of Overcharge Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The steady state potential increased with the charging rate, resulting in increased oxidation (and electronic conductivity) of the polymers. 7 At a current density of 1.0 mA/cm 2 (2.7 C), the separator was able to maintain a voltage of 4.6 V. In this configuration, however, a steady state potential could not be maintained above…”
Section: Rate Capability Of Overcharge Protectionmentioning
confidence: 99%
“…7 The current carrying properties of composite membranes coated with electroactive polymers are influenced by other factors, such as the loading of the polymer, the morphology of the deposited polymer, the porosity of the composite, and the availability of doping anions from the electrolyte. (Fig.…”
Section: Rate Capability Of Overcharge Protectionmentioning
confidence: 99%
“…Various types of electrolyte additives, such as redox shuttles [4][5][6][7][8][9][10][11][12] and polymerizable monomers [13,14], have been proposed to protect the batteries from overcharging, but these additives can not provide sufficient shunting current at high rate charge or cause irreversible damages to batteries. In comparison, the use of electroactive polymer separator to control the charging voltage seems to be a more attractive method for overcharge protection because the polymer can be selected to switch between conductive and insulating states reversibly at required overcharging potentials and sustain sufficient high charging current [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The first electroactive polymer membrane was made of poly (3-butylthiophene) with an oxidation potential about 3.2 V (versus Li + /Li), which is quite low than the charging voltage required for controlling most of the currently used Li-ion batteries [15][16][17][18]. Subsequently, Chen et al [20] and Xiao et al [19] reported different types of bilayer electroactive polymer separators with extended high oxidation potential limits, but the bilayer configuration seems to be much more complicate for preparation and battery applications.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] When incorporated into a microporous separator membrane, the elecroactive polymer remains insulating during normal cell charge and discharge, but it creates a reversible, resistive internal short upon overcharging. 8 The polymer limits the cell potential and protects the cell components from damage without restricting ion transport in the electrolyte or any significant leakage current. A bilayer configuration, in which a polymer with a higher oxidation potential is placed in contact with the cathode to set the protection voltage and a lower voltage polymer is placed next to the anode to protect the high voltage polymer from degradation at the anode potential, was later introduced to expand the operating voltage window in high-energy cells.…”
mentioning
confidence: 99%